A mathematical model of a twin ducted-fan vertical takeoff and landing jetpack. (August 2014) - Speck, Michael; Buchholz, Jörg; Sellier, Mathieu
A dynamic model of a twin ducted-fan vertical takeoff and landing aircraft, the Martin Jetpack, has been developed to study and improve the understanding of the flight mechanics involved with this novel aircraft concept. This article describes the flight mechanics of a twin ducted-fan aircraft and explains in detail the modeling of the forces and moments contributed by the twin ducted-fans, body aerodynamics, control surfaces, gyration, and landing gear interactions. Also, a novel model for the movement of the duct center of pressure has been developed, which allows for the complex duct pitching moment to be predicted. Employing the conventional aircraft modeling methodology, a system of ordinary differential equations that describes the behavior of the aircraft is developed. The equations are solved in real-time using MATLAB–Simulink software to simulate the response to given inputs. A comparison of the flight data with both steady-state (trimmed) and dynamic simulations shows good agreement, which validates the novel duct center of pressure model. The validated model allows the aircraft designer/engineer to efficiently evaluate the sizing of key aerodynamic features and various control methodologies to aid in the design and flying of the Martin Jetpack.